Neurodegeneration of the cornea and retina in patients with type 1 diabetes without clinical evidence of diabetic retinopathy - Carmichael, Josie; Fadavi, Hassan; Tavakoli, Mitra (Frontiers in Endocrinology, 2022)
Aim Diabetic retinopathy (DR) is thought to be the earliest microvascular complication of diabetes. However, recent studies have shown that retinal nerve fiber layer and corneal nerve abnormalities may be present in diabetic patients without retinopathy. This preliminary study aimed to establish if structural and functional fluctuations in the nerve fiber layer of the retina and cornea occur in patients with Type 1 diabetes (T1DM) without retinopathy. Methods Twenty patients with T1DM, without clinical evidence of retinopathy (Age: 47.0±2.5 years; Duration diabetes: 27.0±3 years) and 15 age-matched healthy control subjects underwent detailed medical, neurological examinations. Ophthalmic examinations using Spectral Domain Optical coherence tomography (OCT), Standard Automated Perimetry (SAP) Flicker Defined Form High Edge Perimetry (FDF), Corneal Confocal Microscopy (CCM) and Non-contact corneal Aesthesiometry (NCCA) were performed to quantify the structure and function of the nerves in the retina and cornea, respectively. Results At the structural level, retinal nerve fiber layer thickness (RNFL) was significantly reduced in the superior nasal (P=0.001) and inferior temporal (P=0.004) areas in diabetic patients. Retinal ganglion layer function was decreased in the patient group when assessed using Flickering Defined Perimetry (FDF), but this was not significant. The cornea's function assessed by corneal sensitivity, using a non-contact corneal aesthesiometer (NCCA), was significantly reduced (P=0.001). Structural assessment of corneal nerves using Corneal confocal microscopy showed reduction at corneal nerve fiber density (CNFD) (P=0.01), branch density (CNBD) (P=0.006) and length (CNFL) (P=0.01) in patients with diabetes. Compared to control subjects, the percentage of abnormality in patients with T1DM for RNFL was 32%, while the FDF was abnormal in 61% of patients. Corneal abnormality was observed at 47% for NCCA, 28% for CNFD, and 17% for CNFL. There was no correlation between neuronal damage in the retina and cornea. Conclusions Neuronal abnormalities were observed in the retina and cornea of diabetic patients without evidence of retinopathy. The prevalence of abnormality was higher in the retina, but the severity was greater in the cornea. The results of this preliminary study suggest that structural changes in the cornea and the retina may occur in parallel and correlated with functional changes.